The Prophet’s Mantle and Its Diverse Narratives - Marziye Ramazani Mobarake; Yazdan Farrokhi; Mojtaba Soltani Ahmadi; Mehdi Ebadi (پژوهش های تاریخی)
AbstractThe Burda, believed to be the mantle of Prophet Muhammad (PBUH), is claimed to have served as a symbol of legitimacy for Umayyad and Abbasid caliphs during investitures and other significant events. According to the prevailing narrative, the Burda was passed from Ka’b bin Zuhair to Mu’awiyah and subsequent Umayyad caliphs, eventually reaching the Abbasids, where it remained in Baghdad until the end of the Abbasid Caliphate. It is further asserted that the relic was transferred to Egypt and ultimately to the Ottomans, where it resides today. While the Burda’s fame and significance are widely recognized, its origin and historical trajectory are subjects of considerable debate and uncertainty. This article employed a descriptive and analytical approach, gathering textual data from historical sources through documentary methods coupled with a critical evaluation of relevant scholarship. It investigated the reliability and trustworthiness of the historical narrative concerning the Burda attributed to Prophet Muhammad (PBUH), examining the content of historical texts. The research revealed that this narrative was absent from early historical sources and was fraught with inconsistencies regarding its origin and accessibility. It argued that the caliphate's pressing need for such a symbol had led to the perpetuation of claims about its existence and authenticity, which were reflected in historical texts. Consequently, contemporary researchers had often accepted this narrative uncritically.Keywords: Prophet’s Mantle, Ka’b ibn Zuhair, Ahl-e Ila, Muslim Governors.IntroductionDuring the Abbasid Caliphate, prominent customs and rituals included draping the Burda (mantle), holding the Qadib (staff), and wielding the Saif (sword), particularly during the Bay’ah (oath of allegiance) ceremony for the Caliph. These items were claimed to be part of Prophet Muhammad’s (PBUH) legacy, symbolizing the Caliph’s authority and legitimacy. By utilizing these relics, the Caliphs aimed to present themselves as the rightful successors to the prophet (PBUH) in the eyes of the Muslim community. The possession of these symbols was deemed essential for ascending to the Caliphate, underscoring their significance in legitimizing the ruler’s authority.Given their historical and legitimizing roles, it is important to investigate when and how these symbols came into the possession of the Caliphs. Notably, these relics, especially the Burda, were not directly given to the Caliphs by the prophet (PBUH). Furthermore, numerous contentious accounts exist regarding how the Burda reached the Caliphs, raising questions about the authenticity and historical accuracy of these narratives.The Mafatih al-Ulum encyclopedia authored by Abu Abdullah al-Khwarizmi presents a unique narrative concerning the Burda. It states: “It is the garment or mantle that the Messenger of God (PBUH) bestowed upon the poet Ka’b bin Zuhair and Mu’awiyah purchased it from Ka’b and thereafter the Caliphs inherited it”. Al-Khwarizmi’s account implies the existence of a single Burda—the one given by the prophet (PBUH) to Ka’b, which subsequently passed to Mu’awiyah and then to the Abbasid Caliphs. This narrative has been widely accepted by contemporary historians and is frequently cited in encyclopedias, scholarly articles, and research books. However, as this article demonstrated, this view is inconsistent with the content of early historical texts and established scholarly standards of historical research, rendering its presentation as a definitive “historical proposition” highly questionable. Thus, the central question arises: to what extent are the historical accounts regarding the Burda—claimed by the Caliphs to be attributed to the prophet (PBUH)—historically credible based on the available evidence?Materials & MethodsThis article employed a descriptive and analytical approach, focusing on the collection of data from historical texts through documentary analysis and a critical evaluation of relevant scholarship. The study aimed to differentiate between various narratives, traced their earliest origins in historical texts, and analyzed their evolution over time. By critically examining the sources and their contexts, this research sought to assess the reliability and authenticity of the claims surrounding the Burda.Research FindingsContrary to al-Khwarizmi’s 4th-century AH account regarding the Burda, which he claimed was given by the prophet (PBUH) to Ka’b bin Zuhair—a narrative accepted by some contemporary researchers—this historical proposition was not entirely tenable. Early Hadith sources discussing the Burda do not mention its gifting to Ka’b Ibn Qutaybah Dinawari’s Kitab al-Shi’r wa al-Shu’ara, often cited as the oldest source for this claim, was fundamentally a work of “literary history” rather than historiography or Hadith literature. Consequently, its account was neither widely disseminated nor elaborated upon by later historians. Furthermore, Lata’if al-Ma’arif, the first source to relay Dinawari’s narrative, was not considered an early or reliable source as its content was influenced more by anecdotal and entertaining storytelling than by rigorous historical analysis.Al-Mawardi and Ibn Farra’ were among the first to highlight the disagreements and doubts surrounding the Burda narrative. The existence of “disagreement” among their contemporaries regarding the authenticity of the Burda gifted by the prophet (PBUH) to Ka’b warranted further scrutiny. Some accounts from that era suggested that the Burda in the possession of the Caliphs was the one given by the prophet (PBUH) to the “people of Ayla”, indicating that the Umayyad Caliphs had been deprived of it until the reign of Marwan ibn Muhammad. However, the narrative of the “Burda of the people of Ayla” was itself contentious. In the 7th century AH, Yaqut reported that the people of Ayla claimed to still possess the Burda of the prophet (PBUH). The situation became even more complex with the assertions of Imami Hadith scholars, who maintained that a Burda of the prophet (PBUH) was held by Ali (AS) during his caliphate. The existence of at least 3 competing narratives—the “Burda of Ka’b”, the “Burda of the people of Ayla”, and the “Burda of Ali (AS)”—challenged the authenticity of the Abbasid Caliphs’ claim to the unique Burda of Ka’b.Additionally, historical accounts often mentioned the loss or destruction of the Burda while in the possession of the Abbasid Caliphs. For example, there were reports of its temporary loss to the Seljuks, al-Mas’udi’s account of its disappearance following the assassination of al-Muqtadir and its alleged destruction during Hulagu Khan’s conquest of Baghdad. Iranian historians of the Ilkhanate, who were closer to these events, emphasized the Burda's definitive disappearance, a claim supported by the silence of 7th and 8th-century Mamluk texts. However, references to its presence re-emerged in the 9th and 10th centuries, noting its association with the Abbasid Caliphs in Egypt and later the Ottoman Sultans. Ottoman texts, while corroborating this narrative, offered justifications for the earlier reports of its loss to the Mongols, distinguishing between the “Burda of Ka’b” (lost) and the “Burda of the people of Ayla” (preserved).Discussion of Results & ConclusionThe findings of this research indicated that the acceptance of the Burda as a legitimizing symbol for the Umayyad, Abbasid, and Ottoman rulers was highly contentious when examined through the lens of early historical texts. There was no definitive or unquestionable narrative regarding its transmission to the Caliphs. The claims made by the Abbasids in Egypt and later by the Ottomans lacked convincing evidence and were riddled with inconsistencies. Ultimately, the authenticity of the Burda remained uncertain and historians could only discuss the “perceptions” and “claims” of individuals from each historical period regarding this relic. The narratives surrounding the Burda, rather than reflecting historical facts, revealed the political and symbolic needs of ruling dynasties to legitimize their authority through connections to the prophet (PBUH).